Slip flow on Stagnation Point over a Stretching Sheet in a Viscoelastic Nanofluid - Muhammad Khairul Anuar, Mohamed; Nor Aida Zuraimi, Md Noar; Mohd Zuki, Salleh; Ishak, Anuar (2016)
In this study, the numerical investigation of stagnation point flow past a stretching sheet immersed in a viscoelastic (Walter’s liquid-B model) nanofluid with velocity slip condition and constant wall temperature is considered. The governing equations for the model which is non linear partial differential equations are first transformed by using similarity transformation. Then, the Runge-Kutta-Fehlberg method is employed to solve the transformed ordinary differential equations. Numerical solutions are obtained for the reduced Nusselt number, the Sherwood number and the skin friction coefficient. Further, the effects of slip parameter on the Nusselt number and the Sherwood number are analyzed and discussed. It is found that the heat and mass transfer rate is higher for the Walter’s fluid compared to the classical viscous fluid and the presence of the velocity slip reduces the effects of the stretching parameter on the skin friction coefficient.